(3MOjK aj GdYdd hGdebGUO (B/s - (3WjH, CMeO(B.s ((3GdbGgQIs (3OGQ GdbOS GdYQHjs, 2014)
Islamic law; interpretation and construction.
Keywords: Islamic law; (3Yde GdcdGe(B.s; (3Gdabg GdESdGej, CUhd(B.s; (3GdebGUO GdTQYjI(B.s